2015
DOI: 10.3389/fmicb.2015.00705
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens protection against the action of disinfectants in multispecies biofilms

Abstract: Biofilms constitute the prevalent way of life for microorganisms in both natural and man-made environments. Biofilm-dwelling cells display greater tolerance to antimicrobial agents than those that are free-living, and the mechanisms by which this occurs have been investigated extensively using single-strain axenic models. However, there is growing evidence that interspecies interactions may profoundly alter the response of the community to such toxic exposure. In this paper, we propose an overview of the studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 173 publications
(197 reference statements)
2
84
0
2
Order By: Relevance
“…In mixed‐species biofilms, EPS produced by one species could protect another species against biocides by exacerbating diffusion reaction limitations (Sanchez‐Vizuete et al . ). The protective role of cellulose for S .…”
Section: Discussionmentioning
confidence: 97%
“…In mixed‐species biofilms, EPS produced by one species could protect another species against biocides by exacerbating diffusion reaction limitations (Sanchez‐Vizuete et al . ). The protective role of cellulose for S .…”
Section: Discussionmentioning
confidence: 97%
“…The presence of different microorganisms renders the structure of the biofilm very complex, which has important implications for biofilm eradication and removal. Indeed, multispecies interactions in mixed biofilms are known to affect resistance to disinfectants (3). For instance, the presence of a curli-producing Escherichia coli strain was found to protect Salmonella enterica serovar Typhimurium biofilm cells from chlorine (4).…”
mentioning
confidence: 99%
“…Previous investigations have reported that interspecies interactions that take place within multi-species biofilms significantly modify the matrix composition if compared with monocultures (Giaouris et al 2015;Sanchez-Vizuete et al 2015). This differential composition can affect, among others, the efficacy of enzymes as well as several antimicrobial compounds .…”
mentioning
confidence: 99%